1997
DOI: 10.1212/wnl.49.5.1322
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary endotheliopathy with retinopathy, nephropathy, and stroke(HERNS)

Abstract: We describe a Chinese American family with a hereditary syndrome consisting of retinopathy, nephropathy, and stroke, affecting 11 members spanning three generations. Ophthalmologic evaluations revealed macular edema with capillary dropout and perifoveal microangiopathic telangiectases. Several members had renal abnormalities with proteinuria and hematuria. Initial manifestations were visual impairment and renal dysfunction; neurologic deficits occurred in the third or fourth decade of life. Symptoms included m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
113
1
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 192 publications
(121 citation statements)
references
References 5 publications
6
113
1
1
Order By: Relevance
“…Compared to HSA, these syndromes are less systemic in nature, although hepatic involvement has been suspected in two CRV patients [22,28]. A combination of prominent retinopathy and systemic vasculopathy (HERNS) has been reported in a Chinese family [7]. In contrast to HSA, neither cerebral calcifications nor recurrent seizures have been reported in HERNS patients.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Compared to HSA, these syndromes are less systemic in nature, although hepatic involvement has been suspected in two CRV patients [22,28]. A combination of prominent retinopathy and systemic vasculopathy (HERNS) has been reported in a Chinese family [7]. In contrast to HSA, neither cerebral calcifications nor recurrent seizures have been reported in HERNS patients.…”
Section: Discussionmentioning
confidence: 98%
“…In contrast to HSA, neither cerebral calcifications nor recurrent seizures have been reported in HERNS patients. Furthermore, the clinical symptoms in HERNS patients neither include prominent liver and gastrointestinal dysfunction nor myopathy or cardiopathy [7,21]. An autosomal recessive cerebroretinal vasculopathy with cerebral calcifications has recently been reported in a German sister pair [15,16,20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Magnetic resonance imaging reveals contrast-enhancing subcortical lesions with surrounding edema, especially in the frontoparietal region (Jen et al, 1997). However, the diagnosis is confirmed by genetic analysis.…”
Section: Diagnosismentioning
confidence: 97%
“…Ultrastructural studies revealed alterations in arterioles and capillaries consisting in multilayered basement membrane in the brain and in other tissues such as kidney and skin biopsies (Jen et al, 1997).…”
Section: Hereditary Endotheliopathy With Retinopathy Nephropathy Anmentioning
confidence: 99%